Atmosphere, climate, and change - Graedel, T. E.; Crutzen, Paul J., 1933- (New York : Scientific American Library, 1997)
"In Atmosphere, Climate, and Change, world renowned experts on the chemistry of the atmosphere Thomas E. Graedel and Paul J. Crutzen take us behind the scenes of local climate change to reveal the workings of the atmosphere in its larger context, as a component of Earth as a system. By exploring the causes of long-term climate change and the sources and pitfalls of scientific prediction, they give us a new understanding of what changes are likely to occur in the future, and what can be done about them."--BOOK JACKET
1. Taking the Pulse of Earth -- 2. Agents of Climate -- 3. Chemistry in the Air -- 4. Climates of the Past -- 5. Changing Chemistry -- 6. Predicting the Near Future -- 7. Predicting the Far Future -- 8. Of Change and Sustainability
Includes bibliographical references (pages [177]-182) and index
Keywords: Climatology; Atmospheric chemistry